A note on a mother-foetus pair and alleged father match in the Atlantic fin whale (Balaenoptera physalus) off Iceland - Pampoulie, Christophe; Olafsdottir, Gudbjorg; Hauksdottir, Sigurbjorg; Skirnisdottir, Sigurlaug; Olafsson, Kristinn; Magnusdottir, Steinunn; Chosson, Valerie; Halldorsson, Sverrir Daniel; Olafsdottir, Droplaug; Gunnlaugsson, Thorvaldur; Danielsdottir, Anna K.; Vikingsson, Gisli A. (J. Cetacean Res. Manage., 2023)
The North Atlantic fin whale (Balaenoptera physalus) undertakes long-distance annual migration between high-latitude summer feeding locations and low-latitude winter mating locations, like most of the baleen whales. By statistically comparing genotype profiles of mother-foetus pairs (n = 23) to that of the potential alleged father (n = 139) captured at the same feeding location in Iceland, we found a matching pairing of a mother-foetus captured in 2009 and a father captured in 2010. To our knowledge, the present study is the first one to detect a mother-foetus pair matching with an alleged father, caught at exactly the same feeding area one year later.